2009
DOI: 10.1007/s10719-009-9276-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and enzymatic activity inhibition in cell lines treated with novel iminosugar derivatives

Abstract: Iminosugars are monosaccharide analogues that have been demonstrated to be specific inhibitors for glycosidases and are currently used therapeutically in several human disorders. N-alkylated derivatives of D-fagomine and (2R,3S,4R,5S)-2-(hydroxymethyl)-5-methylpyrrolidine-3,4-diol with aliphatic chains were tested in eight human cancer cell lines to analyze their cytotoxicity and the inhibitory effect in the activities of specific glycosidases. Results indicate that these compounds were more cytotoxic as the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…[1][2][3][4][5][6] The strong electron-withdrawing capacity of fluorine and its marked hydrophobic character induce significant modifications to physicochemical properties, such as solubility, bioavailability, basicity, conformation, and binding properties to a biological target. [10][11][12][13][14][15][16] The latter behave as sugar mimetics by disrupting the natural biological event, mainly through inhibition of glycoenzymes such as glycosidases. [10][11][12][13][14][15][16] The latter behave as sugar mimetics by disrupting the natural biological event, mainly through inhibition of glycoenzymes such as glycosidases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] The strong electron-withdrawing capacity of fluorine and its marked hydrophobic character induce significant modifications to physicochemical properties, such as solubility, bioavailability, basicity, conformation, and binding properties to a biological target. [10][11][12][13][14][15][16] The latter behave as sugar mimetics by disrupting the natural biological event, mainly through inhibition of glycoenzymes such as glycosidases. [10][11][12][13][14][15][16] The latter behave as sugar mimetics by disrupting the natural biological event, mainly through inhibition of glycoenzymes such as glycosidases.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Iminosugars belong to a family of compounds that exhibit therapeutic potential toward several metabolic disorders and act as antiviral, antidiabetic, and antitumor agents. [10][11][12][13][14][15][16] The latter behave as sugar mimetics by disrupting the natural biological event, mainly through inhibition of glycoenzymes such as glycosidases. Structural modification of natural iminosugars has led to "second-generation" drugs that are much more potent and selective, some of which are now on the market.…”
Section: Introductionmentioning
confidence: 99%
“…11 Iminosugar derivatives have been reported to be active against the Flaviviridae viral family, 12 cytotoxic against several cancer cell lines 13 and to inhibit angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…6 Iminosugars were used in metabolic disorders characterized by the accumulation of glycosphingolipids in lysosomes, because of the deficient activity of glycosidases. 7 In particular N -butyl-1-deoxynojirimycin has been used to treat type 1 Gaucher diseases characterized by glucocerebroside accumulation, 8 whereas α-glucosidase inhibitors were used to treat type-2 diabetes mellitus. 9 However, inhibition of carbohydrate-processing enzymes by iminosugars also affects maturation, transport and secretion of glycoproteins involved in cell to cell contact.…”
mentioning
confidence: 99%
“…The results showed that the cytotoxic effect of these compounds was dependent on the length of the alkyl groups attached to the iminosugars and paralleled the inhibitory activity of glycosidases. 7 Moreover, castanospermine, an iminosugar endowed with α-glucosidase inhibitor activity, was shown to inhibit the migration and invasion tendency of tumour cells, preventing them from binding to extracellular matrix. 12, 13 These lines of evidence suggest that iminosugars are endowed with a broad range of biological activity potentially useful in therapeutic treatment.…”
mentioning
confidence: 99%